Effect of multi-walled CNTs polyurethane mats lamination with basalt fabrics reinforced-epoxy composites reviewed on tension and bending properties - Sugiarti, N. W.; Adi Atmika, K.; Ary Subagia, I. D. G. (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Material technology continues to develop with various innovations and engineering to improve weaknesses in both mechanical and physical properties. In this study, electrospun fibres containing a multi-wall blend of CNT and Polyurethane (PU) with or without surfactant that laminated into a basalt fibre-reinforced composite were uniquely demonstrated. Multi-wall CNT 3wt% was added to the PU/MEK/DMF solution and produced using an electrospinning process. PU fibre mat containing 3wt% CNT was made without and with surfactants. Also, Basalt fibre reinforced epoxy composite as a control sample was produced. In addition, vacuum-assisted resin transfer printing has been used in the manufacture of composite panels containing both fibres. The aim of combining basalt fibre and PU CNT spun mats was to investigate their effect on the tensile and flexural mechanical properties. Tensile and flexural tests were carried out on a universal testing machine (UTM) in accordance to ASTM D 638 and ASTM D790 standards. FESEM and TEM on composite morphology test were done after testing. The results indicated that the basal matting fibre-reinforced epoxy composites stacked by PU mats with or without surfactants were affected by CNT inclusions. Nanofiber spun mats laminated in a basalt fibre composite lead to a considerable increase in both loads (i.e. tensile and flexural properties). The highest tensile and flexural load values occurred in the BF+PU-mat-2 sample with triton-x 100 surfactants compared to BFRP. The increase in tensile and flexural modulus values was at 13% and 17.3%, respectively. On the other hand, there was a decrease in shear failure due to tensile and bending loads due to the brittleness of the composite reinforcement. In conclusion, this CNF-mat lamination is highly suitable to be used to improve the strength properties of BFRP composites. It is highly recommended for automotive parts, marine compartments and storage insulation.